Enhancing Research Competence in Distance Education through Scientific Workshops: Integrating Ergo-Iconic Learning Design - Andriyansah, Andriyansah; Sapriati, Amalia; Rulinawaty, Rulinawaty (LifeSciFi, 2026)
Distance education has expanded rapidly with the increasing use of digital technologies. It often presents challenges related to learner engagement, interaction, and the development of practical competencies. Integrating scientific workshops and ergonomic learning design may provide a more interactive and supportive learning environment. This study aims to examine the effectiveness of integrating scientific workshops into distance education to enhance students’ competencies, particularly in supporting the preparation of final research projects. A mixed-methods approach was employed, combining descriptive quantitative analysis with qualitative insights from semi-structured interviews. The study involved 197 participants and data were collected using structured questionnaires and follow-up interviews with selected informants. The quantitative results show that 91.3% of participants gained new knowledge related to TAPM and TAPD, 98.9% reported that the materials supported their final project writing, and 99.5% found the practical training in research tools and output interpretation beneficial. Qualitative findings further indicate that the workshops improved participants’ understanding of research methods and fostered collaborative learning, although some participants experienced difficulties in independently applying the research tools. These findings suggest that integrating scientific workshops with ergo-iconic instructional design can improve engagement, strengthen research competencies, and support more effective learning experiences in distance education environments.